Radiation Damage caused by swift heavy ions in MgO crystals - Баубекова, Г; Асылбаев, Р; Гиниятова, Ш (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The accumulation of structural defects F-type was studied from the spectra of radiation-induced optical absorption for MgO single crystal irradiated by 132Xe ions with fluency of F = 5x10 11 – 3.3x10 14 ион/см 2 . The concentration of F-type defects in MgO crystals were estimated by means of the Smakula formula. The excitation spectra for the luminescence of F + and F centers were also measured. The analysis of ion-induced changes of micro-mechanical properties of the same samples have been performed; the depth profiles of hardening in MgO crystals correlate with the energy loss of Xe ions. A joint contribution of Ionization and elastic collision mechanisms are considered in the formation of F-type centers and extended defects under MgO irradiation with swift heavy ions.